National Public Security System - Venzor Castañeda, Manuel Bernardo (UNIVERSIDAD DE SONORA, 2018)
This document as a final work of the subject Adaptation of the State and Public Administration in Mexico,presents a description of the management modelestablished in accordance with the legal framework and public policies derived from the National Public Security System. The analysis of this model yields conclusions that show a complex, cutting-edge structural and functional design, whith advanced purposes from the perspective of administration and public management. However, the results in reality do not correspond with the efficiency of the legal and administrative design of the system. This makes necessary a general rethinking of the national security strategy.